MAINTAINING OF SOCIAL ENTERPRISE SUSTAINABILITY IN COVID-19 AND POST ERA: AN EXAMINATION OF PERFORMANCE MEASUREMENT METHODS - Nurindrasari, Diana (Jurnal Ekonomika dan Manajemen, 2024)
This study aims to investigate the strategies employed by social enterprises in Indonesia to maintain their sustainability during the Covid-19 pandemic and post era. Social enterprises play a crucial role in addressing societal challenges by combining business approach with social missions and achieving Sustainable Development Goals (SDG’s). However, the COVID-19 has posed significant challenges to the sustainability of these enterprises. The research method involves conducting in-depth interviews with five CEOs from diverse social enterprises operating in Indonesia. The findings are that social enterprises have developed specific performance measurement methods to maintain their agility in the face of crises. These methods are more than traditional financial indicators and encompass broader dimensions such as social impact, environmental sustainability, and community engagement. By employing qualitative methods, social enterprises are able to capture the nuances and complexities of their operations, providing a more comprehensive understanding of their performance.